Historical eye on IPF: a cohort study redefining the mortality scenario - Tomassetti, Sara; Ravaglia, Claudia; Piciucchi, Sara; Ryu, Jay; Wells, Athol; Donati, Luca; Dubini, Alessandra; Klersy, Catherine; Luzzi, Valentina; Gori, Leonardo; Rosi, Elisabetta; Lavorini, Federico; et al. (Frontiers in Medicine, 2023)
Rationale Therapies that slow idiopathic pulmonary fibrosis (IPF) progression are now available and recent studies suggest that the use of antifibrotic therapy may reduce IPF mortality. Objectives The aim of the study was to evaluate whether, to what extent, and for which factors the survival of IPF in a real-life setting has changed in the last 15 years. Methods Historical eye is an observational study of a large cohort of consecutive IPF patients diagnosed and treated in a referral center for ILDs with prospective intention. We recruited all consecutive IPF patients seen at GB Morgagni Hospital, Forlì, Italy between January 2002 and December 2016 (15 years). We used survival analysis methods to describe and model the time to death or lung transplant and Cox regression to model prevalent and incident patient characteristics (time-dependent Cox models were fitted). Measurements and main results The study comprised 634 patients. The year 2012 identifies the time point of mortality shift (HR 0.58, CI 0.46–0.63, p < 0.001). In the more recent cohort, more patients had better preserved lung function, underwent cryobiopsy instead of surgery, and were treated with antifibrotics. Highly significant negative prognostic factors were lung cancer (HR 4.46, 95% CI 3.3–6, p < 0.001), hospitalizations (HR 8.37, 95% CI 6.5–10.7, p < 0.001), and acute exacerbations (HR 8.37, 95% CI 6.52–10.7, p < 0.001). The average antifibrotic treatment effect estimated using propensity score matching showed a significant effect in the reduction of all-cause mortality (ATE coeff −0.23, SE 0.04, p < 0.001), acute exacerbations (ATE coeff −0.15, SE 0.04, p < 0.001), and hospitalizations (ATE coeff −0.15, SE 0.04, p < 0.001) but no effect on lung cancer risk (ATE coeff −0.03, SE 0.03, p = 0.4). Conclusion Antifibrotic drugs significantly impact hospitalizations, acute exacerbations, and IPF survival. After the introduction of cryobiopsy and antifibrotic drugs, the prognosis of IPF patients has significantly improved together with our ability to detect IPF at an earlier stage.